Potential Effect of Pegagan (Centella asiatica (L.) Urban) and Widuri (Calotropis gigantea (L.)) as Immunomodulator - Tias Pramesti Griana (Journal of Food and Pharmaceutical Sciences, 2019)
Abstract: The immune system functions to protect the body from pathogens and cure disease. Even a mild infection will have a bad effect if the host's immune system is not working properly. Modification of the immune response functions to increase and decrease the immune response to overcome disease known as immunomodulation. Immunomodulators are used either as a prevention or treatment of various diseases related to immune disorders. Immunomodulatory drugs change the immune system response by increasing (immunostimulating) or decreasing (immunosuppressive) antibody production. Immunostimulators are given to increase the immune response to infectious diseases, immunodeficiency (e.g. AIDS) and cancer. Immunosuppressive drugs are used to reduce the immune response to transplanted organs and treat autoimmune diseases. The use of medicinal plants to treat various diseases has shown minimal side effects. Natural compounds that are produced from the metabolism of medicinal plants are known to affect the immune system, both the function and production of immune cells, as well as antibody secretion. Indonesia is one of the countries that has used plants as traditional medicine since ancient times. Indonesia 7,000 species of medicinal plants that have been studied to address health problems. Among the medicinal plants that have been studied are Centella asiatica (L.) Urban and Calotropis gigantea (L.) which have been shown to cure various diseases. This review article describes the potential of native Indonesian medicinal plants, namely Centella asiatica (L.) Urban and Calotropis gigantea (L.) as immunomodulators.